Irish voters repealed the eighth: now it's time to ensure access to abortion care in law and in practice. Issue 52 (1st January 2018) - Kasstan, Ben
Abstract: This commentary discusses Ireland's 25 May 2018 Referendum result to repeal the Eighth Amendment and has two key aims. Firstly, it encourages policy-makers to grasp the full potential of legislative reform by enabling and protecting women's access to abortion care within a continuum of sexual and reproductive healthcare options. Secondly, it calls for urgent clarity about access to abortion care in the interim period of legislative transition.